The spectrum of sexual transaction: representations in young Africans' HIV-themed creative narratives. Issue 6 (1st June 2021) - Singleton, Robyn; Sabben, Gaelle; Winskell, Kate
Abstract: Sexual transaction, or any exchange of financial or material goods for sex, contributes to the disproportionate HIV burden among young women aged 15-24 years in sub-Saharan Africa. We analysed representations of sexual transactions in a sample of 363 narratives about HIV written by young Africans. The narratives were written at 4 time points (1997, 2005, 2008, 2014) by authors aged 10-24 years in urban and rural areas of Senegal, Burkina Faso, South-east Nigeria, Kenya and Eswatini, formerly Swaziland. We combined three analytical approaches: descriptive statistics of quantifiable characteristics of the narratives, thematic data analysis and a narrative-based approach. Representations reflect sexual transaction as a spectrum, with commercial sex work and sexual transactions that include romance at opposite ends. Narratives represent female characters increasingly motivated by a desire for social status symbols and by romantic love over time. Condemnation and stigmatisation of sexual transactions motivated by materialism remain similar across countries. In order to mitigate young women's disproportionate risk of HIV there is a need to combine efforts to address the economic marginalisation and gender inequality that drive sexual transactions with activities to promote skills and reflection and influence harmful norms, potentially drawing on companionate ideologies.